Sosialisasi Keselamatan Berkendara Guna Mencegah Kecelakaan Lalu Lintas Di Yayasan Al Kamilah, Serua Bojongsari, Depok - Mohamad Hery Saripudin; Syahrul Salam; Siti Maryam; Sophiana Widiastutie; Pribadi Sutiono; Yuliani Widianingsih (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This socialization aimed to increase participants' knowledge of driving safety. Participants who are students at Al Kamilah Foundation need to be equipped with knowledge related to driving safety because they are at high risk of experiencing road incidents due to negligence.  Youth health and safety are necessary to empower future generations as human resources. The service provided this time was a socialization that took place in a hybrid manner. The participants were students at the Al Kamilah Foundation, Serua Bojongsari, Depok. Socialization was also supported by tracking participants' understanding using pre- and post-test questionnaires. Based on this service, the service team has made efforts to increase participants' knowledge of driving safety.